2010
DOI: 10.1124/dmd.109.031518
|View full text |Cite
|
Sign up to set email alerts
|

Transporter Studies with the 3-O-Sulfate Conjugate of 17α-Ethinylestradiol: Assessment of Human Liver Drug Transporters

Abstract: ABSTRACT:17␣-Ethinylestradiol (EE2), a component of oral contraceptives, is known to undergo considerable first-pass 3-O-sulfation in the intestine and liver. Once formed, the 3-O-sulfate conjugate (EE2-Sul) is detected in circulation at appreciable levels (versus parent EE2) and is present in bile. Therefore, hepatic uptake of EE2-Sul was assessed with suspensions of cryopreserved human primary hepatocytes. In this instance, there was evidence for active (temperature-dependent) uptake, which was described by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 39 publications
4
35
0
Order By: Relevance
“…EE2-Sul can cycle back into the gut (via bile secretion) and be hydrolyzed to parent EE2, or it can be taken up by OATP2B1 therein. At the present time, the mechanism by which EE2-Sul undergoes efflux across the basolateral membrane (from the enterocyte into the portal blood) is unknown, but OST␣ and OST␤ may be the candidate transporters (Han et al, 2010). The fraction of EE2-Sul that survives liver first pass can circulate, can be taken up by OAT3 in the kidney and secreted into urine via both OAT4 and BCRP.…”
Section: Ee2 3-o-sulfate As a Kidney Drug Transporter Substratementioning
confidence: 99%
See 2 more Smart Citations
“…EE2-Sul can cycle back into the gut (via bile secretion) and be hydrolyzed to parent EE2, or it can be taken up by OATP2B1 therein. At the present time, the mechanism by which EE2-Sul undergoes efflux across the basolateral membrane (from the enterocyte into the portal blood) is unknown, but OST␣ and OST␤ may be the candidate transporters (Han et al, 2010). The fraction of EE2-Sul that survives liver first pass can circulate, can be taken up by OAT3 in the kidney and secreted into urine via both OAT4 and BCRP.…”
Section: Ee2 3-o-sulfate As a Kidney Drug Transporter Substratementioning
confidence: 99%
“…It is concluded that circulating EE2-Sul is taken up by OAT3 and effluxed by OAT4 at the brush-border membrane of human renal proximal tubule cells. The latter may function coordinately with BCRP, because EE2-Sul is also a BCRP substrate (Han et al, 2010). Therefore, at least three transporters may play a role in the renal elimination of EE2-Sul.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to EEG, EES systemic exposure was decreased (up to an order of magnitude) in TR Ϫ rats. EES is a BCRP substrate (Han et al, 2010b), so these alterations are primarily attributed to the greatly decreased Bcrp expression and function in TR Ϫ rats (Yue et al, 2011). In the studies presented here, EES biliary excretion in TR Ϫ rat liver perfusions was negligible.…”
Section: Transport Determines Eeg and Ees Pharmacokinetics (49/60)mentioning
confidence: 74%
“…Likewise in mice, the reduction was noted only after oral administration. Although Han et al (2010b) and Chu et al (2004) concluded that EES is not a substrate of MRP2, the Chu et al (2004) study demonstrated a very low level of MRP2 transport activity, although it did not meet the prespecified substrate criteria. The Mrp2-knockout mouse data presented here and the fact that the decrease in EES exposure was greater in TR Ϫ rats than either Mrp2-or Bcrp-knockout mice alone suggest that EES may be a poor Mrp2 substrate and that this transporter by itself has a very modest influence on EES pharmacokinetics.…”
Section: Transport Determines Eeg and Ees Pharmacokinetics (49/60)mentioning
confidence: 99%